Menopause as a regulatory device for matching the demand for children with its supply: A hypothesis - Oded Stark (University of Bonn, Center for Development Research (ZEF), 2021)
Drawing on two assumptions: that menopause is an instrument for the efficient regulation of the duration of a biologically expensive state, and that people have children in order to obtain support from them in old age, we set out a new idea that seeks to explain both the occurrence of menopause and its timing. On the basis of the notion that the purpose of having children is to obtain support in old age, we perceive menopause as an upper limit to the fertile state, when a continued ability to give birth to children would not generate the desired support. The conjecture yields specific testable predictions, and can be assessed against the "reproductive conflict" hypothesis. Being supported by one's offspring is a distinctive feature of humans; in this context, we cannot rely on animal studies in evolutionary biology and related fields to help us to ascertain something that is specific to humans.
Keywords: D64; D90; J13; J14; 330; Occurrence and timing of menopause; Support in old age; Demand for children; Supply of children